2005
DOI: 10.1159/000085710
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Early Failure of Native Arteriovenous Fistulas

Abstract: Introduction: Current guidelines recommend native arteriovenous fistulas (AVF) as the vascular access of choice for hemodialysis on account of the lower incidence of complications. However, this kind of vascular access has a high rate of early failure (early thrombosis or non-maturation). Our aim was to examine whether clear risk factors for early AVF failure could be identified in our patients. Subjects and Methods: Data of all patients who underwent creation of an AVF at the Geneva University Hospital from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
3
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 43 publications
11
97
3
4
Order By: Relevance
“…Perhaps as a result of the close relationship between predictive factors and pathophysiology, the location of the fistula in the lower or upper arm did not factor into our prediction rule because adequate inflow and outflow are required irrespective of fistula location. This is consistent with some studies (18,22), whereas others found improved maturation in upper arm fistulas (12,35). This same reasoning may be applied to gender.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Perhaps as a result of the close relationship between predictive factors and pathophysiology, the location of the fistula in the lower or upper arm did not factor into our prediction rule because adequate inflow and outflow are required irrespective of fistula location. This is consistent with some studies (18,22), whereas others found improved maturation in upper arm fistulas (12,35). This same reasoning may be applied to gender.…”
Section: Discussionsupporting
confidence: 92%
“…The clinical consequences of immature fistulas include prolonged dependence on "bridging catheters" with all of the attendant complications, patient inconvenience, need for further attempts at permanent access surgery, and risk for eventual patient refusal (8,11). Even in programs that use routine preoperative vascular mapping to guide the surgeon's choice of access type and location, primary failure still occurs in a subset of patients (12,13). In promoting fistula creation and use, it would be ideal to be able to predict which patients would benefit from an AVF that would mature successfully, without excessive intervention, and to tailor access placement accordingly.…”
mentioning
confidence: 99%
“…Studies conflict regarding the association between women, AVF nonmaturation, and reduced patency (6)(7)(8)(9), which is hypothesized to be related to smaller diameter veins in women compared with men. This is difficult to assess, because many studies do not perform preoperative vein mapping or report vein diameters.…”
Section: Demographicsmentioning
confidence: 99%
“…18,19 There is evidence suggesting an increased failure in smaller radiocephalic fistulas, or cases with increased steal syndrome, which were attributed to microvascular damage associated with diabetes; these may not be relevant due to the numerous confounding factors associated with this population. 20,21 Our small sample size is a limitation of our study and conclusions based on these results are limited. However, the conclusions drawn from the results support and add to existing evidence.…”
Section: Discussionmentioning
confidence: 82%